Daikenchuto (TU‐100) alters murine hepatic and intestinal drug metabolizing enzymes in an in vivo dietary model: effects of gender and withdrawal. Issue 5 (3rd October 2017) - Nobutani, Kentaro; Miyoshi, Jun; Musch, Mark W.; Nishiyama, Mitsue; Watanabe, Junko; Kaneko, Atsushi; Yamamoto, Masahiro; Yoshida, Masaru; Kono, Toru; Jeong, Hyunyoung; Chang, Eugene B.
Abstract: Herbal medicines and natural products used for maintenance of health or treatment of diseases have many biological effects, including altering the pharmacokinetics and metabolism of other medications. Daikenchuto (TU‐100), an aqueous extract of ginger, ginseng, and Japanese green pepper fruit, is a commonly prescribed Kampo (Japanese herbal medicine) for postoperative ileus or bloating. The effects of TU‐100 on drug metabolism have not been investigated. In this study, we analyzed the effect of TU‐100 on expression of key drug‐metabolizing enzymes (DMEs) and drug transporters (DTs) in murine liver and gastrointestinal tract using a dietary model. Liver, jejunum, and proximal colon were analyzed for phase I and II DMEs and DT mRNA expression by reverse transcription (RT) first by nonquantitative and followed by quantitative polymerase chain reaction (PCR) and protein expression. Liver, jejunum, and proximal colon expressed some identical but also unique DMEs and DTs. TU‐100 increased the greatest changes in cytochrome (Cyp) 2b10 and Cyp3a11 and Mdr1a. Basal and TU‐100 stimulated levels of DME and DT expression were gender‐dependent, dose‐dependent and reversible after cessation of TU‐100 supplementation, except for some changes in the intestine. Quantitative Western blot analysis of protein extracts confirmed the quantitative PCR results.